ANALISIS KELAYAKAN USAHA GREEN POLYBAG DARI LIMBAH INDUSTRI KELAPA SAWIT - M. Indra Darmawan; Jaka Darma Jaya; Adzani Ghani Ilmannafian; Rika Safitri (Universitas Galuh Ciamis, 2020)
Green polybag is one result of the utilization of palm oil waste. Green polybag which is eco-friendly will be needed, so it has opportunity to be marketable comodity. This study aimed to determine the business feasibility of establishing green polybag business. Data were collected by observation, interview and documentation. The method used were analysis of technical aspects, analysis of economic aspects based on the calculation of business feasibility namely Break Event Point (BEP) production, BEP rupiah, Return On Investment (ROI), Payback Period (PBP) and Benefit Cost Ratio (B / C), analysis of market aspects and sensitivity analysis. Analysis of technical aspects show that the availability of raw materials were sufficient, the equipment used was feasible and the processing method was easy. Based on economic aspects the results of BEP production was 4.216.58, BEP rupiah was Rp.5.059.897.66, ROI was 12.17%, PBP was 7.86 months and B / C was 1.13. Analysis of market aspects showed that the prospect of a green polybag business has a great opportunity based on none competitors. Sensitivity analysis based on the assumption of an increase in wages of labor with a percentage of 8.34% per year of business was feasible, assuming an increase in the cost of tapioca flour with a percentage of 3.5%, 3% and 3% were also said feasible based on B / C value ratio> 1.